Marsupial Genetics and Genomics - Waters, Paul D.; Deakin, Janine E.; Marshall Graves, Jennifer A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Marsupials belong to the Class Mammalia, sharing some features with other mammals, yet they also possess many unique features. It is their differences from the more traditionally studied mammals, such as mice and humans, that is of greatest value to comparative studies. Sequencing of genomes from two distantly related marsupials, the short grey-tailed opossum from South America and the Australian tammar wallaby, has launched marsupials into the genomics era and accelerated the rate of progress in marsupial research. With the current worldwide concern for the plight of the endangered Tasmanian devil, marsupial genetics and genomics research is even more important than ever if this species is to be saved from extinction. This volume recounts some of the history of research in this field and highlights the most recent advances in the many different areas of marsupial genetics and genomics research.
Marsupial Breeding -- Breeding and Genetic Management of Captive Marsupial Populations -- Marsupial Chromosomes and Gene Maps -- The Conserved Marsupial Karyotype: Chromosome Painting and Evolution -- Marsupial Centomeres and Telomeres: Dynamic Chromosome Domains -- Marsupial Linkage Maps -- Physical and Comparative Gene Maps in Marsupials -- Marsupial Genome Sequencing -- Marsupial Sequencing Projects and Bioinformatics Challenges -- Insight into Evolution of Gene Regulation Networks from the Opossum Genome -- Marsupial Sex Chromosomes -- Organization and Evolution of the Marsupial X Chromosome -- Gene Content of the Mammalian X Chromosome -- Marsupial Sex Chromosome Behaviour During Male Meiosis -- Compact but Complex – The Marsupial Y Chromosome -- Marsupial Epigenetics -- The Evolution of Genomic Imprinting – A Marsupial Perspective -- Marsupial Genetics Reveals Insights into Evolution of Mammalian X Chromosome Inactivation -- Marsupial Reproductive and Developmental Genetics -- Molecular Regulation of Marsupial Reproduction and Development -- Marsupial Milk – Identifying Signals for Regulating Mammary Function and Development of the Young -- Marsupial Immune Genes -- The Marsupial Major Histocompatibility Complex -- Marsupial Immunoglobulin and T Cell Receptor Genomics -- Use of Genomic Information to Gain Insights into Immune Function in Marsupials: A Review of Divergent Immune Genes -- Marsupial Genes and Gene Evolution -- Visual Pigments and Colour Vision in Marsupials and Monotremes -- The Evolutionary History of Globin Genes: Insights from Marsupials and Monotremes -- The Olfactory Receptor Gene Family of Marsupials -- Marsupial Conservation Genetics -- Marsupial Population and Conservation Genetics -- Devil Facial Tumour Disease (DFTD): Using Genetics and Genomics to Investigate Infectious Disease in an Endangered Marsupial.
Keywords: Animal genetics; Animal Genetics and Genomics